Social representations of Chilean workers regarding labor inclusion of individuals aged 55 and over - Chavira Trujillo, Gabriel; Juanillo Maluenda, Hugo; Palacios Rodríguez, Oscar; León Laurent, Nicolás (Revista Cubana de Salud y Trabajo, 2024)
Introduction: Population aging is a phenomenon that has reconsidered the needs of work environments. The increase in older people is a global trend, particularly in Latin America, so understanding the phenomenon of inclusion is a relevant edge to interpret the Social Representations that workers have about labor inclusion. Objective: To interpret the Social Representations that workers have about the labor inclusion of people aged 55 and over in the Chilean context through a mixed concurrent analysis. Methods: A cross-sectional study was carried out semi-structured interviews to 229 participants with a mean age of 38.44 years and a standard deviation of 11.69; 92.58% were men. Results: The words "Experience" and "Opportunity" are the most prevalent in the central nucleus of the representation. The experience has related inclusive meanings with the time at work, while the opportunity word represents the inclusion in work spaces and the chance to be able to live with the most experienced. Conclusions: The similarity of the arguments of the participants, points out the criteria in workers related to inclusion of individuals aged 55 and over and providing elements for understanding the phenomenon and its determinants